Family Medicine Services for Elderly Women with Uncontrolled Grade II Hypertension and Obesity - Anggita Gardeesna Sari; Fitria Saftarina (CV. Jasa Sukses Abadi, 2021)
Hypertension is an abnormal increase in blood pressure which can be a major cause of cardiovascular disease. It is a condition characterized by systolic blood pressure> 140 mmHg and / or diastolic blood pressure> 90 mmHg. The prevalence of hypertension in Indonesia occurs in the age group 31-44 years (31.6%), age 45-54 years (45.3%), age 55-64 years (55.2%). One of the risk factors associated with hypertension is obesity. Every 1 kg of increase in body weight has a HR for suffering from hypertension of 1.36 (95% CI: 1.29-1.45). In addition, based on the results of previous studies, it shows that every kilogram of weight loss can reduce systolic blood pressure by 1.05 mmHG and diastolic by 0.92 mmHg. Hypertension can be controlled by improving modifiable risk factors. This is the reason for comprehensive management of hypertensive patients with risk factors for obesity, in order to prevent serious complications in patients that lead to decreased quality of life of patients both within the family and community.